Analisa Prediksi Harga Emas Dengan Kemungkinan Terjadinya Resesi Menggunakan Metode SVR - Fevrierdo Nathaniel Shanahan Pradana; Frederik Samuel Papilaya (Prahasta Publisher, 2023)
Gold is a resource that has a high value and has the advantage of a stable selling price. This can be proven by the choice of gold which is often used as a long-term investment tool. It can be seen that the impact of Covid-19 and the Russia-Ukraine war is considered to be the causes of recession that will affect the economy and end with the changes of gold selling price. This research was conducted on the basis of the large number of people who are now starting to be interested in investing in gold. However, this is quite a question for gold investors because of economic changes from the impact of Covid-19 and the Russia-Ukraine war. People are certainly worried, especially for those who have investments in the form of gold. The purpose of this research is to provide an analysis in the form of predictions of gold prices in 2023, an advice on managing gold in the future. The method used is the Support Vector Regression method using a polynomial kernel and supported by the Mean Absolute Percentage Error measurement. From the past research that has been done, the prediction results for gold prices in 2023 with an error value of 4.8% where this value is in the very good category. From this research, several suggestions are also given in managing gold during a recession